UPAYA PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN SEKSUAL: (Studi Kasus Desa Bumiharjo, Kecamatan Glenmore, Kabupaten Banyuwangi) - Surya Wulandari; Lukman Hakim; Abdul Aziz (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Sexual violence against children is a serious issue that involves multiple dimensions, including social, legal, religious, and others. One case of child sexual violence was uncovered in Bumiharjo Village, Glenmore District, Banyuwangi Regency, but it is reasonable to assume that there are still other cases that have not been reported due to fear and lack of understanding of reporting procedures. This study aims to explore the existing legal protections, identify various obstacles in their implementation, and formulate necessary corrective measures. An empirical legal approach was employed in this research, using techniques such as interviews, observation, and document analysis. The findings indicate that despite the availability of reporting services, child protection efforts are still hindered by a lack of education, weak supervision of non-formal education, and minimal family involvement. Therefore, it is crucial to strengthen relevant institutions in providing continuous education and fostering partnerships between the government, community, and families. The handling process is further hampered by social pressures, the perpetrator’s status as a religious figure, and insufficient ongoing assistance. This study underscores the importance of inter-agency coordination, the strengthening of rehabilitation systems, and public education in creating an effective legal protection system that prioritizes the best interests of the child.